Program Innovation in the National Amil Zakat Management System: A Step Towards Enhancing the Welfare of Mustahik - Rozi, Muhammad Fakrur; Mashudi; Qomarul Huda (Universitas Muhammadiyah Sidoarjo, 2024)
The continued development of the ZIS management system which gave birth to new programs which are the result of the program innovations of each amil zakat institution is expected to be able to improve the welfare of mustahik in various fields. This study aims to find out the collection, distribution, utilization and reporting of zakat, infaq, alms (ZIS) funds at BAZNAS Tulungagung and NU Care-LAZISNU Tulungagung. This research method is qualitative with descriptive research type, data collection techniques with in-depth interviews, moderate participation observation and documentation, data analysis model of Miles and Huberman. Checking the validity of the data by extending observations, increasing persistence, triangulation and member checks. The results of this study are 1) collection at BAZNAS Tulungagung through UPZ, Bank Transfers, Counters/counters, by conducting outreach to agencies and social media Instagram Facebook and YouTube while NU Care- LAZISNU Tulungagung through the MWC, Twigs and congregation, bank transfers, zakat car, with socialization to congregations, and social media Instagram Facebook and WhatsApp groups. 2) Distribution of BAZNAS Tulungagung through education compensation programs, medicine for Islamic boarding schools, mass circumcision, house renovations, and Zakat Community Development (ZCD) for tourist villages while NU Care- LAZISNU Tulungagung through education care programs, free medical treatment, disaster response, mosque construction, programs wholesale. 3) Utilization of BAZNAS Tulungagung through a basic food distribution program for orphans totaling 1500 pcs each year, One Family One Bachelor scholarship (SKSS) at 4 universities in Tulungagung for underprivileged families,